Contrasting cybersecurity implementation frameworks (CIF) from three countries. (8th July 2019) - Dedeke, Adenekan; Masterson, Katherine
Abstract : Purpose: This paper aims to explore the evolution of a trend in which countries are developing or adopting cybersecurity implementation frameworks that are intended to be used nationally. This paper contrasts the cybersecurity frameworks that have been developed in three countries, namely, Australia, UK and USA. Design/methodology/approach: The paper uses literature review and qualitative document analysis for the study. The paper developed and used an assessment matrix as its coding protocol. The contents of the three cybersecurity frameworks were then scored to capture the degree to which they covered the themes/items of the cybersecurity assessment matrix. Findings: The analysis found that the three cybersecurity frameworks are oriented toward the risk management approach. However, the frameworks also had notable differences with regard to the security domains that they cover. For example, one of the frameworks did not offer guidelines with regard to what to do to respond to attacks or to plan for recovery. Originality/value: The results of this study are beneficial to policymakers in the three countries targeted, as they are able to gain insights about how their cybersecurity frameworks compares to those of the other two countries. Such knowledge would be useful as decision-makers take steps to improve their existing frameworks. The results of this study are also beneficial to executives who have branches in all three countries. In such cases, security professionals could deploy the most comprehensive framework across all three countries and then extend the deployment in each location to meet country-specific requirements.